Arthroscopic Treatment of a Case with Concomitant Subacromial and Subdeltoid Synovial Chondromatosis and Labrum Tear - Nevres Hurriyet Aydogan; Onur Kocadal; Ahmet Ozmeric; Cem Nuri Aktekin (Case Reports in Orthopedics)
Synovial chondromatosis is a disease that seldomly seen in shoulder joint and is related to benign synovial proliferation and synchronous chondral tissue formation within the joint cavity. Patients suffer from progressive restriction of range of motion and shoulder pain. Extra-articular involvement is an extremely rare condition. Degenerative osteoarthritis, joint subluxation, and bursitis are common complications in untreated patients. Open or arthroscopic surgery is suitable while there is no consensus related to superiority of different approaches. We presented an arthroscopic treatment of a male patient, 48 years old with labrum tear and synovial chondromatosis localized in subacromial and subdeltoid region. Advantages of arthroscopic surgery in the presence of intra- and extra-articular combined pathologies are also discussed.